Results of 250 consecutive cadaver kidney transplants. Issue 6009 (6th March 1976) - Hall, C L; Sansom, J R; Obeid, M; Blainey, J D; Robinson, B H; Mackintosh, P; Dawson-Edwards, P; Barnes, A D
Abstract : The results of 250 cadaver kidney transplants performed at this hospital between May 1968 and December 1974 were analysed. A functioning transplant was defined strictly as one that maintained the recipient in good health with a serum creatinine below 442 mumol/1 (5 mg/100 ml) without any need for dialysis. The proportions of kidneys functioning after one, two, and three years were 40-4%, 33-9%, and 31-1% respectively, the corresponding survival rates of patients being 62-6%, 57-4%, and 43-8%. The primary failure rate overall was 21-6%, while the failure rates for first, second, and third transplants were 18-1%, 39-9%, and 66-7% respectively. Half of the primary failures were attributed to the use of cadaver kidneys with abnormal vasculature or long ischaemic times or originating from non-ventilated donors. Of the initially successful transplants 49% were subsequently lost due to rejection (53%) or death of the patient with a functioning transplant (46%), and of the secondary losses 58% occurred within three months of transplantation. HLA matching of donor and recipient for two or more antigens was associated with a significant increase in transplant survival--46% at three years as opposed to 9-5% at three years for kidneys with poorer matches.